Strategi Komunikasi Pemasaran Penyelenggara Perjalanan Ibadah Umrah (PPIU) Zafa Tour (Studi Fenomenologi Marketer Pejuang Baitullah Dengan Marketer Pejuang Ujroh) - Erwin Rochmansyah; Depi Putri; Purna Irawan (STAI Bumi Silampari, 2025)
Competition between the Umrah pilgrimage travel industry (PPIU) is increasingly competitive and has developed very massively today. This is evidenced by the emergence of many Umrah Travel companies that claim to be official Umrah pilgrimage organizers or have not yet obtained complete legality. This study aims to analyze the marketing strategy of the Umrah pilgrimage travel organizer marketer PT Zafa Mulia Mandiri by highlighting the transactional phenomenon between Baitullah fighter marketers and Ujroh fighter marketers. This study uses a qualitative approach and as a scalpel uses phenomenological theory, and digs up information data in the field through in-depth interview techniques with 4 (four) informants based on their own perceptions and this data is obtained through interview techniques with questions that have been prepared in advance. In addition to interviews, researchers also conducted participant observation and other documentation recordings. The results of the study revealed that there were incidents of transaction activity problems between marketers who were truly Baitullah fighters who merely carried out amaliah and hoped for blessings from God. In addition, researchers also found that Ujroh fighter marketers violated business ethics by seizing pilgrims who had been prospected by previous marketers. The study concluded that the marketing strategy of Umrah travel marketers can be distinguished from fighting for the intent and purpose as an Umrah marketer, whether only to expect blessings and rewards for inviting people to the Baitullah or only to gain profit.